Inflammasome polymorphisms in juvenile systemic lupus erythematosus. (3rd October 2015) - Pontillo, Alessandra; Reis, Edione C.; Liphaus, Bernadete L.; Silva, Clovis A.; Carneiro-Sampaio, Magda
Abstract: Inflammasome is the cytoplasmic complex responsible for pro-IL1 β cleavage and secretion of IL-1β. Recently our group reported the first association between polymorphisms in the inflammasome receptor NLRP1 and adult-onset systemic lupus erythematosus (SLE) " di per se " and especially in SLE-associated renal disease, suggesting the involvement of NLRP1-inflammasome in the immune dysregulation characteristic of SLE patients. Considering that juvenile-onset SLE (JSLE) is more severe than adult SLE, and that the genetic background plays a major role in the early development of autoimmune diseases, we analysed selected polymorphisms in inflammasome genes ( NLRP1, NLRP3, CARD8, IL1B, TNFAIP3 ) of children and adolescents with JSLE ( n  = 90) and in healthy controls ( n  = 144). A single polymorphism in IL1B, and not NLRP1, gene resulted in association with JSLE, suggesting that IL-1 β is involved in the pathogenesis of SLE, but different genes could play specific role in adult- or early-onset disease.